Impact of maedi-visna on sheep breeding flocks - Jones, Scott (2021)
Maedi-visna (MV), is a chronic wasting disease of sheep and goats caused by the small ruminant lentivirus (SRLV), maedi-visna virus (MVV). With no known cure or treatment, an asymptomatic period of sometimes several years and an infection that ultimately results in death, the finding that prevalence is on the rise within the UK is of great concern.